Changes in Electrocardiographic Findings with Aging in a Longitudinal Study of 500 Apparently Healthy Persons Aged 60 Years and Older - Nakamura, Yoshiro; Kawamura, Masahide; Shinmura, Ken; Ebihara, Yoshinori; Tani, Masato (Nihon Rōnen Igakkai zasshi, 1994)
A number of studies have been published which have attemped to define the electrocardiographic (ECG) changes with aging, but most of them were obtained from cross-sectional studies. To distinguish ECG changes related to physiological aging from those associated with arteriosclerosis, we assessed the ECG changes of 500 apparently healthy subjects, aged 60 years and older in 1992, who had been followed at the Keio Health Consulting Center for over 15 years. All subjects had no overt cardiovascular diseases in 1992. We compared the ECG in 1992 with that taken over 15 years ago. Changes in ECG during that period were also reviewed. With aging, the mean axis deviated to the left, the mean QTc interval was shortened, and the mean PR interval was prolonged. ST segmental change, atrial overloading, bundle branch block developed newly in 16%, 8% and 7% of, respectively. There were no relationships among axis deviation, PR interval change, or QTc shortening and coronary risk factors. QTc prolongation and ST segmental change were strongly related to hypertension or impaired glucose tolerance. When ECG changes in those under 65 years old were compared with those over 80 years old, the incidence of ST segmental change in those over 80 years old was significant higher. This study was not a prospective study but suggested each type of ECG change related to aging was affected by physiological and/or pathological factors in a distinct way and had different phases of development and progression.